2021
DOI: 10.1093/hsw/hlab003
|View full text |Cite
|
Sign up to set email alerts
|

Desired Characteristics of HIV Testing and Counseling among Diverse Survivors of Intimate Partner Violence Receiving Social Services

Abstract: Despite recent calls to integrate HIV testing into social services addressing intimate partner violence (IPV), few studies have reported on survivors’ perspectives regarding the desired characteristics of this integration. The purpose of this study was to describe desired characteristics of HIV and sexually transmitted infection (STI) testing services from a survivor’s perspective. A qualitative descriptive approach was taken to describe the perspectives of IPV survivors who may or may not have accessed this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Not valuing women as more powerful than or equally powerful to others not experiencing abuse Murray et al, 2018;Storer & Casey, 2021) was not a response found as frequently as the other stigmatizing responses (n = 6). When they searched for help, some professionals pitied them (Gonzalez-Guarda et al, 2021). Other women would not seek help in order to avoid experiencing stigma from their employers and co-workers who thought they were passive.…”
Section: Loss Of Statusmentioning
confidence: 99%
“…Not valuing women as more powerful than or equally powerful to others not experiencing abuse Murray et al, 2018;Storer & Casey, 2021) was not a response found as frequently as the other stigmatizing responses (n = 6). When they searched for help, some professionals pitied them (Gonzalez-Guarda et al, 2021). Other women would not seek help in order to avoid experiencing stigma from their employers and co-workers who thought they were passive.…”
Section: Loss Of Statusmentioning
confidence: 99%